Nutritional status and health profile among single mothers in Malaysia - Sakinah, Harith; Noor Aini, Mohd Yusoff; Shariza, A.R; Teoh, C.M (2017)
According to the Population and Housing Census, Department of Statistics Malaysia, there are 126,810 single mothers among the 11·4 million women in Malaysia with Selangor has the highest number of single mothers (16,748) in the country(1) . Meanwhile, the amount of single mothers in Kelantan has been increased to 70,000 people, comprising both divorcees and widows. There are a total number of 16,344 single mothers whose aged less than 59 years old and 25,110 single mothers with the age range of more than 60 years old that are registered under Kelantan Secretariat of Women, Family and Welfare in 2014. The objective of this cross-sectional study is to determine the nutritional status and health profile of single mothers in Kota Bharu, Kelantan. A total of 100 single mothers aged 18–59 years old were involved in this study. Assessment of blood glucose, blood pressure, height and weight were done to each respondent. Food consumption based on the 24-hours diet recall was recorded and analyzed using Nutritionist Pro™ version 5.4·0 software.